Gene Expression of Aquaporins (AQPs) in Cumulus Oocytes Complex and Embryo of Cattle - Julieth M. Petano-Duque; Rafael E. Castro-Vargas; Juan S. Cruz-Mendez; Kelly J. Lozano-Villegas; María P. Herrera-Sánchez; Heinner F. Uribe-García; Juan S. Naranjo-Gómez; Rafael J. Otero-Arroyo; Iang S. Rondón-Barragán (Animals, 2022)
Aquaporins (AQPs) are proteins with various functions related to proper cell function and early development in mammals. The aim of this study was to evaluate the presence of AQPs and determine their mRNA levels in the cumulus oocyte complex (COC) of four bovine breeds and in blastocysts of five bovine crosses. Grade I, II and III COCs were collected by ovum pick up from non-lactating heifers of the Brahaman, Holstein, Gir and Romosinuano breeds. Embryos were produced in vitro up to the blastocyst stage of the bovine ♀Gir × ♂Holstein, ♀Holstein × ♂Gir, ♀Brahman × ♂Holstein, ♀Holstein × ♂Brahman, and ♀Romosinuano × ♂Holstein crosses. mRNA expression of AQP1-AQP12b was estimated in COC and embryos by real-time-PCR. The presence of the twelve AQPs in the COCs and bovine embryos was established. Additionally, significant differences were determined in the expression of AQP6 and AQP12b in COCs, as well as in transcripts levels of AQP4, AQP8 and AQP9 from bovine embryos. Gene expression of AQPs in COCs and bovine embryos is consistent with the previously described biological functions. This is the first report of AQPs in COC of Gir, Brahman, Holstein and Romosinuano and embryos of five crossbreeds between Bos indicus and B. taurus.